A Multifunction Power Converter With Multimode Capabilities for Low Power Electric Vehicles - Maurya, Virendra Prasad; Singh, Rajeev Kumar (IEEE transactions on power electronics, 2025)
This article proposes a multifunction power converter with multimode capability for the low-power electric vehicle (EV). In multifunction, a single converter provides single-phase on-board charging, motoring, vehicle-to-vehicle (V2V) charging operation, and multiple supplies for EV auxiliaries. In the multimode, the multioutput features of the proposed converter are utilized for functionalities of V2V charging and auxiliary supplies, along with motoring and single-phase charging. Single-phase charging maintains the unity power factor at the source terminal while charging the battery with a constant-current, constant-voltage charging technique and generates three outputs. The first dc (48 V) charges the battery, and two other outputs (12 and 72 V) are used for auxiliary power supply. During the motoring mode also, it generates the three outputs from the 48-V battery. The first ac output drives the brushless dc motor (BLDC) motor by the existing high pulsewidth modulation low- on switching technique, and the other two outputs (12 and 72 V) cater to the auxiliary power demand of the cabin. The 72-V of the multioutput of the proposed converter is also utilized with V2V charging. The 12-V regulated output eliminates the need for an additional 12-V battery and its charger for the low-power auxiliaries of EVs. Furthermore, the 72-V regulated output decreases the current requirement to feed the high-power auxiliaries. To justify the merits of the proposed converter, multifunction and multimode operation, parameter selection, control algorithm, comparative analysis, loss analysis, and the experimental result with load dynamic are presented in this article. A laboratory scale prototype is developed, which tested 780 W in charging mode, 1000 W in motoring mode, and 480 W during V2V changing operation.